A calculus problem by Rocco Dalto

Calculus Level pending

{ d x d t = 3 x 2 y 3 z d y d t = x + 2 y 3 z d z d t = x z \begin{cases} \dfrac{dx}{dt} = 3x - 2y - 3z \\ \dfrac{dy}{dt} = x + 2y - 3z \\ \dfrac{dz}{dt} = x - z \end{cases}

The general solution to the above differential system is as follows:

{ x ( t ) = c 1 x 1 ( t ) + c 2 x 2 ( t ) + c 3 x 3 ( t ) y ( t ) = c 1 y 1 ( t ) + c 2 y 2 ( t ) + c 3 y 3 ( t ) z ( t ) = c 1 z 1 ( t ) + c 2 z 2 ( t ) + c 3 z 3 ( t ) \begin{cases} x(t) = c_{1}x_{1}(t) + c_{2}x_{2}(t) + c_{3}x_{3}(t) \\ y(t) = c_{1}y_{1}(t) + c_{2} y_{2}(t) + c_{3}y_{3}(t) \\ z(t) = c_{1}z_{1}(t) + c_{2}z_{2}(t) + c_{3}z_{3}(t) \end{cases} where x j ( t ) y j ( t ) z j ( t ) = A j B j C j e λ j t \begin{vmatrix}{x_{j}(t)} \\{y_{j}(t)} \\ {z_{j}(t)} \\ \end{vmatrix} = \begin{vmatrix}{A_{j}} \\{B_{j}} \\ {C_{j}} \\ \end{vmatrix} * e^{\lambda_{j} t}

for ( 1 < = j < = 3 ) (1 <= j <= 3) .

If C 1 = 1 , C 2 = 1 , C 3 = 1 C_{1} = 1, \: C_{2} = 1, \: C_{3} = 1 and x ( 0 ) = 1 x(0) = 1 , y ( 0 ) = 2 y(0) = 2 , and z ( 0 ) = 3 z(0) = 3 . Find c 1 + c 2 + c 3 c_{1} + c_{2} + c_{3} .

H i n t : Hint: The eigenvalues are λ 1 R \lambda_{1} \in \mathbb{R} and λ 2 , λ 3 = a ± b i \lambda_{2}, \lambda_{3} = a \pm bi .


The answer is -3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
May 13, 2017

Let x ( t ) = A e λ t x(t) = A * e^{\lambda t} y ( t ) = B e λ t y(t) = B * e^{\lambda t} z ( t ) = C e λ t z(t) = C * e^{\lambda t}

d x d t = λ A e λ t , d y d t = λ B e λ t , d x d t = λ C e λ t \implies \dfrac{dx}{dt} = \lambda * A * e^{\lambda t}, \: \dfrac{dy}{dt} = \lambda * B * e^{\lambda t}, \: \dfrac{dx}{dt} = \lambda * C * e^{\lambda t}

Replacing the above in the differential system we obtain the system:

[ 3 λ 2 3 1 2 λ 3 1 0 1 λ ] A B C = 0 0 0 \begin{bmatrix}{3 - \lambda} && {-2} && {-3}\\ {1} && {2 - \lambda} && {-3}\\ {1} && {0} && {-1 - \lambda} \end{bmatrix} * \begin{vmatrix}{A} \\{B} \\ {C} \\ \end{vmatrix} = \begin{vmatrix}{0} \\{0} \\ {0} \\ \end{vmatrix}

We want a nontrivial solution so let det ( [ 3 λ 2 3 1 2 λ 3 1 0 1 λ ] ) = 0 \det(\begin{bmatrix}{3 - \lambda} && {-2} && {-3}\\ {1} && {2 - \lambda} && {-3}\\ {1} && {0} && {-1 - \lambda} \end{bmatrix}) = 0

\implies

λ 3 4 λ 2 + 6 λ 4 = ( λ 2 ) ( λ 2 2 λ + 2 ) = 0 λ = 2 , 1 ± i \lambda^3 - 4\lambda^2 + 6\lambda - 4 = (\lambda - 2) * (\lambda^2 - 2\lambda + 2) = 0 \implies \lambda = 2, \: 1 \pm i

For λ = 2 \lambda = 2 we obtain the system:

[ 1 2 3 0 1 0 3 0 1 0 3 0 ] \left[ \begin{array}{ccc|c} 1 & -2 & -3 & 0\\ 1 & 0 & -3 & 0\\ 1 & 0 & -3 & 0 \\ \ \end{array} \right]

Using row operations we obtain:

B 1 = 0 B_{1} = 0 , A 1 3 C 1 = 0 A_{1} - 3 C_{1} = 0

Letting C 1 = 1 A 1 = 3 C_{1} = 1 \implies A_{1} = 3 \implies

x 1 ( t ) = 3 e 2 t x_{1}(t) = 3 e^{2t} y 1 ( t ) = 0 y_{1}(t) = 0 z 1 ( t ) = e t z_{1}(t) = e^{t}

For λ = 1 + i \lambda = 1 + i we obtain the system:

[ 2 i 2 3 0 1 1 i 3 0 1 0 2 i 0 ] \left[ \begin{array}{ccc|c} 2 - i & -2 & -3 & 0\\ 1 & 1 - i & -3 & 0\\ 1 & 0 & -2 - i & 0 \\ \ \end{array} \right]

Using row operations we obtain:

A 2 ( 2 + i ) C 2 = 0 A_{2} - (2 + i) C_{2} = 0 , B 2 C 2 = 0 B_{2} - C_{2} = 0

Letting C 2 = 1 B 2 = 1 A 2 = 2 + i C_{2} = 1 \implies B_{2} = 1 \implies A_{2} = 2 + i

A 2 B 2 C 2 = 2 + i 1 1 \begin{vmatrix}{A_{2}} \\{B_{2}} \\ {C_{2}} \\ \end{vmatrix} = \begin{vmatrix}{2 + i} \\{1} \\ {1} \\ \end{vmatrix}

Although it is not needed, for λ = 1 i \lambda = 1 - i we obtain:

A 3 B 3 C 3 = 2 i 1 1 \begin{vmatrix}{A_{3}} \\{B_{3}} \\ {C_{3}} \\ \end{vmatrix} = \begin{vmatrix}{2 - i} \\{1} \\ {1} \\ \end{vmatrix}

λ = 1 + i \lambda = 1 + i \implies

2 + i 1 1 = 2 1 1 + 1 0 0 i \begin{vmatrix}{2 + i} \\{1} \\ {1} \\ \end{vmatrix} = \begin{vmatrix}{2} \\{1} \\ {1} \\ \end{vmatrix} + \begin{vmatrix}{1} \\{0} \\ {0} \\ \end{vmatrix} i \implies

V = c 2 e t ( 2 1 1 c o s ( t ) 1 0 0 s i n ( t ) ) + c 3 e t ( 2 1 1 s i n ( t ) + 1 0 0 c o s ( t ) ) = \vec{V} = c_{2} e^{t} * ( \begin{vmatrix}{2} \\{1} \\ {1} \\ \end{vmatrix} cos(t) - \begin{vmatrix}{1} \\{0} \\ {0} \\ \end{vmatrix} sin(t)) + c_{3} e^{t} * ( \begin{vmatrix}{2} \\{1} \\ {1} \\ \end{vmatrix} sin(t) + \begin{vmatrix}{1} \\{0} \\ {0} \\ \end{vmatrix} cos(t)) =

c 2 e t ( 2 c o s ( t ) s i n ( t ) c o s ( t ) c o s ( t ) + c 3 e t 2 s i n ( t ) + c o s ( t ) s i n ( t ) s i n ( t ) c_{2} e^{t} * (\begin{vmatrix}{2 cos(t) - sin(t)} \\{cos(t)} \\ {cos(t)} \\ \end{vmatrix} + c_{3} e^{t} * \begin{vmatrix}{2 sin(t) + cos(t)} \\{sin(t)} \\ {sin(t)} \\ \end{vmatrix}

\therefore The general solution is:

{ x ( t ) = 3 c 1 e 2 t + e t [ c 2 ( 2 c o s ( t ) s i n ( t ) ) + c 3 ( 2 s i n ( t ) + c o s ( t ) ) ] y ( t ) = e t ( c 2 c o s ( t ) + c 3 s i n ( t ) ) z ( t ) = c 1 e 2 t + e t ( c 2 c o s ( t ) + c 3 s i n ( t ) ) \begin{cases} x(t) = 3 * c_{1} * e^{2t} + e^{t} [c_{2} * (2 cos(t) - sin(t)) + c_{3} * (2 sin(t) + cos(t))] \\ y(t) = e^{t} (c_{2} * cos(t) + c_{3} * sin(t)) \\ z(t) = c_{1} * e^{2t} + e^{t} (c_{2} * cos(t) + c_{3} * sin(t)) \end{cases}

For x ( 0 ) = 1 , y ( 0 ) = 2 , z ( 0 ) = 3 x(0) = 1, \: y(0) = 2, \: z(0) = 3 \implies

3 c 1 + 2 c 2 + c 3 = 1 3 * c_{1} + 2 * c_{2} + c_{3} = 1 c 2 = 2 c_{2} = 2 c 1 + c 2 = 3 c_{1} + c_{2} = 3

c 2 = 2 c 1 = 1 c 3 = 6 \implies c_{2} = 2 \implies c_{1} = 1 \implies c_{3} = -6 \implies

c 1 + c 2 + c 3 = 3 c_{1} + c_{2} + c_{3} = \boxed{-3}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...